PAIN MANAGEMENT OF PATIENTS WITH CHRONIC RENAL FAILURE: A CASE STUDY OF PATIENTS IN A PRIVATE RENAL FACILITY IN KWAZULU-NATAL. - Govender, Shamanie; Singh, Karishma; Coopoosamy, Roger; Adam, Jamila Kathoon (Student’s Journal of Health Research Africa, 2024)
Background Pain management in chronic kidney disease patients is extremely complicated. An estimated 82% of patients with chronic kidney disease have moderate to severe pain. The purpose of this study was to investigate the types, frequency, and severity of pain experienced by patients with chronic kidney disease, as well as to suggest strategies that patients and staff could use to manage the patient’s pain. Methods At the Durban Kidney and Dialysis Centre, 60 patients were given questionnaires to assess their level of pain severity and management control. The participants were subjected to inclusion and exclusion criteria. The patient’s medical records were examined. The research was carried out between September 2017 and March 2018. For analysis, relevant statistical methods were used. Patients were all on hemodialysis and averaged 57 years old. Results According to the findings of this study, most patients reported pain symptoms during dialysis, and 72.3% of the pain experienced was moderate to severe, indicating that pain is a major symptom burden in this patient population. Conclusion Both patients and staff would benefit from learning about different types of pain management therapies (both pharmacological and non-pharmacological), as well as the long-term consequences of pain going undiagnosed and untreated. Recommendations The results show that pain is a major symptom burden but the use of analgesics is under-prescribed. Pain management, interventions, and strategies should be a research priority because pain is a valid and considerable health concern in the increasing CKD patient population.